Tailoring bisphosphonate-doped titanium films to optimally couple cellular responses and antibacterial activity for biomedical applications - Dias, Leonardo F G [UNESP]; Costa, Raphael C.; Sacramento, Catharina M.; Ruiz, Karina G S; Barão, Valentim A R; Lisboa-Filho, Paulo N. [UNESP] (American Vacuum Society, 2024)
Titanium (Ti) is widely utilized as an implant material; nonetheless, its integration with bone tissue faces limitations due to a patient's comorbidities. To address this challenge, we employed a strategic approach involving the growth of thin films by spin-coating and surface functionalization with etidronate (ETI), alendronate (ALE), and risedronate (RIS). Our methodology involved coating of Ti cp IV disks with thin films of TiO2, hydroxyapatite (HA), and their combinations (1:1 and 1:2 v/v), followed by surface functionalization with ETI, ALE, and RIS. Bisphosphonate-doped films were evaluated in terms of surface morphology and physical-chemical properties by techniques such as electron microscopy, confocal microscopy, and x-ray photoelectron spectroscopy. The antibacterial potential of bisphosphonates alone or functionalized onto the Ti surface was tested against Staphylococcus aureus biofilms. Primary human bone mesenchymal stem cells were used to determine in vitro cell metabolism and mineralization. Although RIS alone did not demonstrate any antibacterial effect as verified by minimum inhibitory concentration assay, when Ti surfaces were functionalized with RIS, partial inhibition of Staphylococcus aureus growth was noted, probably because of the physical-chemical surface properties. Furthermore, samples comprising TiO2/HA (1:1 and 1:2 v/v) showcased an enhancement in the metabolism of nondifferentiated cells and can potentially enhance the differentiation of osteoblastic precursors. All samples demonstrated cell viability higher than 80%. Addition of hydroxyapatite and presence of bisphosphonates increase the metabolic activity and the mineralization of human bone mesenchymal cells. While these findings hold promise, it is necessary to conduct further studies to evaluate the system's performance in vivo and ensure its long-term safety. This research marks a significant stride toward optimizing the efficacy of titanium implants through tailored surface modifications.